RanBPM is expressed in synaptic layers of the mammalian retina and binds to metabotropic glutamate receptors. - Seebahn, Angela; Rose, Melanie; Enz, Ralf (FEBS letters, 2008)
In the central nervous system, synaptic signal transduction depends on the regulation of neurotransmitter receptors by interacting proteins. Here, we searched for proteins interacting with two metabotropic glutamate receptor type 8 isoforms (mGlu8a and mGlu8b) and identified RanBPM. RanBPM is expressed in several brain regions, including the retina. There, RanBPM is restricted to the inner plexiform layer where it co-localizes with the mGlu8b isoform and processes of cholinergic amacrine cells expressing mGlu2 receptors. RanBPM interacts with mGlu2 and other group II and group III receptors, except mGlu6. Our data suggest that RanBPM might be associated with mGlu receptors at synaptic sites. © 2008 Federation of European Biochemical Societies.
UnivIS-Import:2017-12-18:Pub.2008.med.IB.profes_1.ranbpm
Keywords: mGlu2; mGlu8b; Protein interaction; RanBP9; RanBPM; Retina